Effect of pre- and post-harvest treatments on yield, quality and post-harvest shelf life of king chilli (Capsicum chinense Jacquin) under foothill conditions of Nagaland (India) - V B Singh, C S Maiti, I Rongsennungla, S P Kanaujia, (Journal of Spices and Aromatic Crops, 2012)
Field and laboratory experiments were carried out at Medziphema (Nagaland) to evaluate the effect of pre- and post-harvest treatments on yield, quality and post-harvest life of King chilli (Capsicum chinense Jacquin) under foothill conditions of Nagaland. Highest fresh yield (13.65 t ha-1) and capsaicin content (819421.13 SHU) of fruits were recorded with application of Naphthalene Acetic Acid (40 ppm). Maximum vitamin C content (115.67 mg 100g-1 of fruit) was recorded with application of Ethrel 250 ppm. Lowest physiological loss in weight (2.55%) and change in fruit colour (10%), highest value of ascorbic acid content (120.5 mg 100 g-1 of fruit) and longest shelflife (9 days) were recorded at 9th day after storage in calcium chloride (0.5%) treated fruits, packed in non-perforated bags and stored under refrigeration at 5oC.